The Marinopyrroles, Antibiotics of an Unprecedented Structure Class from a Marine Streptomyces sp - Hughes, Chambers C. (2008)
[Image: see text] Cultivation of an obligate marine Streptomyces strain has furnished the marinopyrroles A and B, densely halogenated, axially chiral metabolites that contain an uncommon bispyrrole structure. X-ray analysis of marinopyrrole B showed that the natural product exists as an atropo-enantiomer with the M-configuration. Though configurationally stable at room temperature, M-(−)-marinopyrrole A can be racemized at elevated temperatures to yield the non-natural P-(+)-atropo-enantiomer. The marinopyrroles possess potent antibiotic activities against methicillin-resistant Staphylococcus aureus.